Respuesta :
We have to evaluate the summation of (3n+2), with n ranging from 1 to 14. Let's write all the terms of the sum for each value of n:
n=1: [tex] 3n+2 = 3\cdot 1+2=5[/tex]
n=2: [tex]3n+2 = 3\cdot 2+2=8[/tex]
n=3: [tex]3n+2 = 3\cdot 3+2=11[/tex]
n=4: [tex]3n+2 = 3\cdot 4+2=14[/tex]
n=5: [tex]3n+2 = 3\cdot 5+2=17[/tex]
n=6: [tex]3n+2 = 3\cdot 6+2=20[/tex]
n=7: [tex]3n+2 = 3\cdot 7+2=23[/tex]
n=8: [tex]3n+2 = 3\cdot 8+2=26[/tex]
n=9: [tex]3n+2 = 3\cdot 9+2=29[/tex]
n=10: [tex]3n+2 = 3\cdot 10+2=32[/tex]
n=11: [tex]3n+2 = 3\cdot 11+2=35[/tex]
n=12: [tex]3n+2 = 3\cdot 12+2=38[/tex]
n=13: [tex]3n+2 = 3\cdot 13+2=41[/tex]
n=14: [tex] 3n+2 = 3\cdot 14+2=44[/tex]
Now, let's sum all the terms together, and we get:
[tex]S=5+8+11+14+17+20+23+26+29+32+35+38+41+44=343[/tex]
n=1: [tex] 3n+2 = 3\cdot 1+2=5[/tex]
n=2: [tex]3n+2 = 3\cdot 2+2=8[/tex]
n=3: [tex]3n+2 = 3\cdot 3+2=11[/tex]
n=4: [tex]3n+2 = 3\cdot 4+2=14[/tex]
n=5: [tex]3n+2 = 3\cdot 5+2=17[/tex]
n=6: [tex]3n+2 = 3\cdot 6+2=20[/tex]
n=7: [tex]3n+2 = 3\cdot 7+2=23[/tex]
n=8: [tex]3n+2 = 3\cdot 8+2=26[/tex]
n=9: [tex]3n+2 = 3\cdot 9+2=29[/tex]
n=10: [tex]3n+2 = 3\cdot 10+2=32[/tex]
n=11: [tex]3n+2 = 3\cdot 11+2=35[/tex]
n=12: [tex]3n+2 = 3\cdot 12+2=38[/tex]
n=13: [tex]3n+2 = 3\cdot 13+2=41[/tex]
n=14: [tex] 3n+2 = 3\cdot 14+2=44[/tex]
Now, let's sum all the terms together, and we get:
[tex]S=5+8+11+14+17+20+23+26+29+32+35+38+41+44=343[/tex]
Answer:
343
Step-by-step explanation:
WE are to evaluate the sum of
[tex]3n+2[/tex] from n=1 to 14
Symbolically this can be reprsented as
[tex]S=\Sigma _{n=1} ^{14} (3n+2)[/tex]
Splitting this into two separate terms we have
[tex]S=\Sigma _{n=1} ^{14} 3n+\Sigma _{n=1} ^{14} 2[/tex]
Since in I term 3 is a constant 3 can be taken out and similarly for II term if 2 taken out it becomes sum of 1, 14 times
[tex]S=3\Sigma _{n=1} ^{14} n+ 28\\[/tex]
The first term is sum of 14 natural numbers and we use the formula
Sum =[tex]3(\frac{14*15}{2} )+2(14)\\=343[/tex]